Pengaruh Pemangkasan Cabang Lateral Terhadap Hasil Polong Segar Tanaman Kacang Panjang (Vigna sinensis L.) - IVAN SUGANDA SIMANJUNTAK; ANAK AGUNG MADE ASTININGSIH; IDA AYU MAYUN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
The effect of pruning on the results of long bean pods (Vigna sinensis L.) Long beans, including leguminosae family in the form of shrubs that grow creepy and easily planted on lowland and highland land, both in the fields of paddyfields, moorlands, and in the yard. Long bean plants are included in indeterminate plants, the vegetative phase continues to be active even though it has entered the generative phase. The lateral branch of the long bean plant continues to grow, so pruning is needed. This study aims to determine the effect of lateral branch pruning on the results of long bean pods. The method used is a test method with a paired system. The treatment tested is trimming the lateral branches and without trimming the lateral branches. Each treatment was repeated 25 times and each replication was represented by 3 plants. Data were analyzed using t-test. The results showed that pruning had an effect on increasing pod yield.